1993
DOI: 10.1038/jcbfm.1993.56
|View full text |Cite
|
Sign up to set email alerts
|

PET Study of Changes in Local Brain Hemodynamics and Oxygen Metabolism after Unilateral Middle Cerebral Artery Occlusion in Baboons

Abstract: Summary: Local cerebral hemodynamics and oxygen metabolism were measured by positron emission tomog raphy (PET) with the oxygen-15 C50) steady-state method in baboons, immediately before (TO), 1 (Tl), and 3-4 (T2) h after permanent middle cerebral artery occlu sion (MCAO). At Tl, there was a marked fall in both cerebral blood flow (CBF) and the CBF/cerebral blood volume (CBV) ratio in the occluded territory; these changes were sustained at T2, indicating stable reduction in cerebral perfusion pressure and lack… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
53
2

Year Published

1996
1996
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(68 citation statements)
references
References 29 publications
13
53
2
Order By: Relevance
“…Our findings that the glucose consumption rate is more or less preserved in parts of the acute ischemic tissue is in accordance with the preserved oxygen consumption rate that has been observed in cats and baboons in the early phase after induction of ischemia (29,30). In the case of oxygen, the reduced delivery (cerebral blood flow) is compensated by an elevated oxygen extraction fraction.…”
Section: Need For Kinetic Modeling In Disease Modelssupporting
confidence: 90%
See 1 more Smart Citation
“…Our findings that the glucose consumption rate is more or less preserved in parts of the acute ischemic tissue is in accordance with the preserved oxygen consumption rate that has been observed in cats and baboons in the early phase after induction of ischemia (29,30). In the case of oxygen, the reduced delivery (cerebral blood flow) is compensated by an elevated oxygen extraction fraction.…”
Section: Need For Kinetic Modeling In Disease Modelssupporting
confidence: 90%
“…Blood was extracted from a catheter placed in the femoral artery with a rate of 0.48 mL/min until 2 min after 18 F-FDG injection. The catheter was then shortened, and discrete blood samples were taken at 3,5,10,20,30,45, and 60 min. Sample radioactivity was measured in a CompuGamma CS g-counter (LKB Wallac, Wallac Oy), and sample volume was determined by consecutive weighing.…”
Section: Blood Samplingmentioning
confidence: 99%
“…Watabe et al (2002) showed that CBF images can be quantitated at much shorter interval than the previous protocol, typically at 90 secs, from sequential PET scanning Altman et al (1991) obtained OEF values of 0.5370.13 from arteriosinus blood sampling. Using steady-state PET, others have measured OEFs ranging from 0.42 to 0.58 in normal tissues of anesthetized monkeys (Altman et al, 1991;Pappata et al, 1993;Touzani et al, 1995;Young et al, 1996;Schumann et al, 1996;Frykholm et al, 2000). Moreover, the values of gCBF in the present PET study were 3079 mL 100/g min from three-step ARG, 3079 mL 100/g min from Previously reported values varied from 27 to 37 mL 100/g min for CBF and 2.4 to 3.4 mL 100/g min for CMRO 2 (Altman et al, 1991;Pappata et al, 1993;Touzani et al, 1995;Young et al, 1996;Schumann et al, 1996;Frykholm et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Using steady-state PET, others have measured OEFs ranging from 0.42 to 0.58 in normal tissues of anesthetized monkeys (Altman et al, 1991;Pappata et al, 1993;Touzani et al, 1995;Young et al, 1996;Schumann et al, 1996;Frykholm et al, 2000). Moreover, the values of gCBF in the present PET study were 3079 mL 100/g min from three-step ARG, 3079 mL 100/g min from Previously reported values varied from 27 to 37 mL 100/g min for CBF and 2.4 to 3.4 mL 100/g min for CMRO 2 (Altman et al, 1991;Pappata et al, 1993;Touzani et al, 1995;Young et al, 1996;Schumann et al, 1996;Frykholm et al, 2000). Variations are because of the differences in monkey species, physiologic conditions, anesthetic agent used, PET scanner, and methodology; the current results clearly show that the DARG method can be used to determine these physiologic parameters with a high degree of accuracy.…”
Section: Discussionmentioning
confidence: 99%
“…Re cent developments in functional imaging technolo gies enable such changes to be followed noninva sively even in small animals. With high-resolution pos itron emission tomography (PET), regional cerebral blood flow (rCBF), regional metabolic rate for oxy gen (rCMR02), and glucose (rCMRglc) can be mea sured repeatedly before and after occlusion of the middle cerebral artery (MCA) in baboons (Tenjin et a!., 1992;Pappata et a!., 1993) and in cats , and the development of the penumbra and the eventual progression to infarction can be followed. We have used repeat determinations of rCBF, rCMR02, and rCMRglc by PET in transient MCA occlusion (MCAO) and related the observed temporal and spatial patterns of changes in flow and energy metabolism to those observed in a few cases during and after thrombolytic therapy.…”
mentioning
confidence: 99%